Predicting Surgical Success in Patients with Idiopathic Epiretinal Membrane Using the Spectral-Domain Optical Coherence Tomography Segmentation Module for Single Retinal Layer Analysis. (3rd August 2018) - Kromer, Robert; Vogt, Clara; Wagenfeld, Lars; Spitzer, Martin Stephan; Stemplewitz, Birthe
ABSTRACT: Introduction: Idiopathic epiretinal membrane (ERM) is a proliferation of cells formed on the internal surface of the retina and may cause a slow decrease in visual acuity (VA). The aim of this study was to evaluate the individual layers of the retina by optical coherence tomography (OCT) before and after vitrectomy with ERM peeling in order to refine surgical decision-making. Methods: Forty-seven eyes of 45 patients (aged 55–87 years) with ERM were enrolled retrospectively from a tertiary referral center. OCT examination was performed preoperatively and at a mean of 3.2 months postoperatively in all cases. Nine retinal surfaces were subjected to automated all-layer segmentation using the manufacturer's software and assessed for their correlation with VA. Results: There was a significant correlation between the initial retinal morphology and change in VA postoperatively. Patients who gained at least two lines of VA had a significantly higher total retinal perimacular volume and retinal nerve fiber layer (each p  < 0.0001) preoperatively. Conclusion: Patients with high preoperative retinal volumes and therefore increased tractive components seemed to benefit more from surgery than those with low tractive components.